2005
DOI: 10.1111/j.1475-097x.2004.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning effect of isokinetic measurements in healthy subjects, and reliability and comparability of Biodex and Lido dynamometers

Abstract: The aim of this study was to examine the learning effect during a set of isokinetic measurements, to evaluate the reliability of the Biodex System 3 PRO dynamometer, and to compare the Biodex System 3 PRO and the Lido Active dynamometers on both extension and flexion over the elbow and the knee at 60 degrees s(-1). Thirteen (nine women, four men) healthy participants were measured five times using the Biodex and once using the Lido dynamometer. The intervals between the first four tests were 20 min, and 1 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
110
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(117 citation statements)
references
References 28 publications
(46 reference statements)
5
110
2
Order By: Relevance
“…Furthermore, it cannot distinguish true change from measurement error (Singer and Willett 2003). Test-retest reliability for Biodex measurements has been previously reported to be high (Lund et al 2005). Also, no learning effects were observed for the Biodex measurements.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Furthermore, it cannot distinguish true change from measurement error (Singer and Willett 2003). Test-retest reliability for Biodex measurements has been previously reported to be high (Lund et al 2005). Also, no learning effects were observed for the Biodex measurements.…”
Section: Discussionmentioning
confidence: 66%
“…Also, no learning effects were observed for the Biodex measurements. Measurement error was 11.75 Nm for the isokinetic strength at 60°/s based on the reported findings in Lund et al (2005). Interpretation of the change in PT dynamic60°s hould therefore be made taking these results into account, as should the changes in other strength performance parameters.…”
Section: Discussionmentioning
confidence: 90%
“…They repeated the measurements 72 hours to 1 week later and found that ICC ranged from 0.59 to 0.74. Lund et al 10) used an isokinetic dynamometer (BIODEX) to measure the strength of extension and flexion of the knee and elbow of 13 healthy men and women with an average age of 32 years. They repeated the measurements after intervals of 20 h and 1 week and reported that ICC ranged from 0.96 to 0.98 for the 3 rd and 4 th measurements taken 20 minutes apart and ranged from 0.89 to 0.97 for measurements taken 1 week apart.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Agre et al 8) using 4 healthy subjects and 3 raters, Pearson correlation coefficients for interrater measurements ranged from -0.19 to 0.96 for the lower extremity, and from 0.88 to 0.94 for the upper extremity. Regarding the limitations of measurements using a hand-held dynamometer(HHD), Hyde et al 10) claimed that, regardless of the tester's experience or power of resistance, 30 kg is the limit, while Wiles et al 11) and Roebeck et al 12) , claimed respectively that it is difficult to maintain the position of the HHD at forces of 300 N and 85 Nm or higher.…”
Section: Introductionmentioning
confidence: 99%
“…31 The primary outcome measure was isokinetic knee extension peak torque values, with estimation of 150 (36) Nm for subjects without hip OA and 105 (37) Nm for patients with hip OA. 32 Based on 5% significance level and 90% power, 17 subjects were needed to be included in each group. If a subject in 1 of the 2 groups dropped out from a test, the matched pair was excluded.…”
Section: Discussionmentioning
confidence: 99%